Case Report: Pancreatic and hepatic kaposiform hemangioendothelioma presenting as consumptive coagulopathy and right hepatic atrophy - Ai, Chengbo; Qiu, Tong; Zhou, Jiangyuan; Wang, Chuan; Song, Jiulin; Pu, Siyu; Jin, Shuguang (Frontiers in Oncology, 2023)
Kaposiform hemangioendothelioma (KHE) is a rare vascular tumor that causes progressive angiogenesis and lymphangiogenesis, which often occurs in the skin or soft tissue, with an acute onset and rapid progression. A 4-year-old girl was admitted to our hospital with a 2-year history of thrombocytopenia, combined with right hepatic atrophy and pancreatic lesion for 3 months. After treatment with gamma globulin and steroids, the platelet count normalized, but it dropped immediately at lower doses. One year after the cessation of hormone therapy, the patient presented with abdominal pain and abnormal liver function and the magnetic resonance imaging (MRI) revealed right hepatic atrophy and pancreatic occupancy, but the first liver biopsy did not reveal any positive pathological results. By analyzing the clinical manifestations in conjunction with MRI and abnormal coagulation, we considered that the patient might be diagnosed as KHE with Kasabach-Merritt phenomenon, however, sirolimus treatment was ineffective and pancreatic biopsy only showed a tendency for tumors of vascular origin. Finally, we performed a Whipple operation after the right hepatic artery embolization, histological and immunohistochemical examination suggested KHE. Three months postoperatively, the patient's liver function, pancreatic enzymes and blood clotting function gradually returned to normal. KHEs may result in significant blood loss with worsening of the coagulopathy and functional impairment, timely surgical intervention for KHE is necessary when non-invasive or minimally invasive treatment is ineffective, or the symptoms of tumor compression are obvious.